Hydrodynamic Modeling of Porous Media; Analytical model ofWater Filtration - S.Mustafa, Ayad; W. Abood, Dheyaa (Iraqi Journal of Civil Engineering, 2008)
Hydrodynamic modeling of viscous flow in porous media was investigated for fourselected filter media crushed silica, crushed anthracite coal, glass beads and crushed garnet.Typical constants that can be used to estimate head loss for some of the most common designof granular media filters were correlated. The effect of several parameters such as porosity(35%-60%) , temperature(20oC-80oC) and media grain size (0.5-2mm) was studied. Empiricalrelationships were developed using a plot of friction vs. Reynolds number similar to those thathad been successfully used for the flow of fluids in pipes. Analytical models were made todevelop an equation for viscous turbulent flow in porous media from first hydraulic principles.Empirical equation was developed to predict pressure drop in porous media as a function ofbed porosity and evaluated the friction factor as a function to flow type.